2009
DOI: 10.1007/s11483-009-9131-x
|View full text |Cite
|
Sign up to set email alerts
|

Microbeam X-ray Diffraction Study of Granular Crystals Formed in Water-in-Oil Emulsion

Abstract: Margarine and fat spread contain typical water-in-oil emulsions, including semi-solid fats, as continuous oil phases. The application of palm oil, one of the most promising trans-fat alternatives, for semi-solid fats is increasing. However, granular crystals often occur in palm-oil-based solid fats and cause deterioration. In this study, we carried out differential scanning calorimetry (DSC), optical microscopy, and X-ray diffraction (XRD) experiments on granular crystals in margarine. A conventional laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 28 publications
(25 reference statements)
0
30
0
Order By: Relevance
“…Many studies were conducted to clarify the mechanism of granular crystal formation in palm oil-based products. They have suggested the possibility of a relationship between the transformation to the β-form and the formation of granular crystals in margarine (Ishikawa et al, 1980, Watanabe et al, 1992, Miura and Konishi, 2001, Sato 2001, Walstra et al, 2001, Tanaka et al, 2007, Tanaka et al, 2009. Information on crystallization behavior, including the polymorphic transition, is therefore important for the fat food industry.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies were conducted to clarify the mechanism of granular crystal formation in palm oil-based products. They have suggested the possibility of a relationship between the transformation to the β-form and the formation of granular crystals in margarine (Ishikawa et al, 1980, Watanabe et al, 1992, Miura and Konishi, 2001, Sato 2001, Walstra et al, 2001, Tanaka et al, 2007, Tanaka et al, 2009. Information on crystallization behavior, including the polymorphic transition, is therefore important for the fat food industry.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1.18 shows the formation of granular crystals in a model margarine containing the oil and fat phase (70% in total), including fully-hydrogenated rapeseed oil (2 wt.%), soybean oil (48 wt.%) and palm oil (20 wt.%). It is evident that granular crystals grew over 5 days under thermal thawing between 7 • C and 15 • C for every 12 hours, and the DSC heating thermogram of the granular crystal portions showed a large melting peak around 23 • C (Tanaka et al, 2009). Conventional XRD study of the granular crystals showed that β-fat crystals of a TCL structure melted below the melting of β -fat of a DCL structure.…”
Section: Fats In Water-in-oil Emulsionsmentioning
confidence: 99%
“…However, the fat crystals of the DCL and TCL structures were simultaneously observed in the central region of a granular crystal (region B, position 2 long spacing values of 6.2 nm and 4.2 nm and 3.1 nm), whereas the fat crystals of the TCL were predominantly present in an outer region of a granular crystal (region C, position 6.2 nm and 3.1 nm). From these results, the microstructures and the formation processes of granular crystals are closely related to the fractional crystallisation of the β form of POP promoted by crystallisation and transformation of PPP and SSS fractions (Tanaka et al, 2009). Various ways of preventing crystallisation and transformation into the β form in margarine and fat spread have been developed, through many techniques, as reviewed by Chrysan (Chrysan, 2005).…”
Section: Fats In Water-in-oil Emulsionsmentioning
confidence: 99%
“…The functionality of fat crystals in margarine is twofold. The essential condition needed to obtain a template effect to induce nucleation is by having a structural similarity between the hydrophobic tail of the surfactant and the TAGs (i.e., similar chain lengths and/or molecular structure) (Tanaka et al, 2009; Water droplet The formation of the fat crystals at the interface may be originated by means of a surfactant (i.e., saturated/ unsaturated mono-and diacylglycerols), which may act as a template that promotes the interfacial heterogeneous nucleation (by reducing the activation energy of nucleation) of the TAGs present in the lipid phase (Wassell et al, 2012;Douaire et al, 2014).…”
Section: Structure and Properties Of Margarine And Low-fat Spreadsmentioning
confidence: 99%